Animação computadorizada: a imagem em movimento expandida nos meios de comunicação digitais - Andrade, Daniel Grizante de (2007)
The objective of this thesis is the research and mapping of the changes undergone by animation with the increased use of computer technology in the creative and productive processes and the advent of new digital communication media. Due to the range of the term animation, an historical-evolutive line known as authorial animation was priorized. For this, contemporary works of animation with innovative use of computer technology were analyzed, including works from artists such as Mark Napier, Marius Watz, Zachary Lieberman, Ckoe, Hans Hoogerbrugge and Motomichi Nakamura, as well as animation series for the Internet such as Stainboy, Ninjai and Cinema Bulbo, and movies such as Waking Life, Ryan, Ghost in the Shell Innocence, among others. The analysis is based on Deleuze s theory of moving images (from which animation is not distinguished), as production of thought that result in a subtle relationship between language, media, technology, poetic intentions, esthetics and ethics, revealing true forms of reflection. From this analysis, three major themes, all extremely important for the comprehension of this kind of computer animation, emerged: the movement created through code, the synthetic moving image and the new media in animation and its influence on the creative process. It was established that Animation a language historically connected with technological media - occupies today an im-portant place in current audiovisual production since its approach of movement is fully compati-ble with contemporary concepts of constructing moving images